Cytokine profiles of phakic and pseudophakic eyes with primary retinal detachment. Issue 4 (18th December 2018) - Garweg, Justus G.; Zandi, Souska; Pfister, Isabel; Rieben, Robert; Skowronska, Magdalena; Tappeiner, Christoph
Abstract: Purpose: To compare the cytokine profiles of phakic (p) and pseudophakic (ps) eyes with primary rhegmatogenous retinal detachment (RD) to eyes with macular holes (MH) and to identify differences in the specific cytokine profiles. Methods: Aqueous humour (AH) and vitreous fluid (VF) were obtained from patients with primary RD without proliferative vitreoretinopathy undergoing vitrectomy. AH and VF of patients with macular holes (MH) served as controls. Forty‐three different cytokines were quantified using multiplex cytokine analysis. Intergroup and intragroup comparisons were performed. To control for multiple comparisons, Holm's correction was applied. Results: VF and AH samples of 71 eyes with RD (pRD N = 38; psRD N = 33) and 26 eyes with MH were included. Cytokine levels in psRD and pRD were similar (none with >10‐fold difference). The levels of 39 of 43 cytokines in the VF were significantly higher in eyes with RD than in those with MH (>10‐fold: CXLC5, CCL26, CCL1, IL‐6, CXCL11, CCL7, CCL13, MIG/CXCL9, CCL19 and TGF‐ β 1). In the AH, 23 of 43 cytokines were significantly higher compared to MH (>10‐fold: CXCL5, IL‐4, IL‐6, IL‐8/CXCL8 and CCL7). Conclusion: A complex, but nonspecific cytokine environmental response seems to initiate immunological and profibrotic processes following RD. Relevant differences in the cytokine profiles of eyes with pRD and psRD were not identified, whereas cytokine differences between AH and VF in RD could be explained by upregulation in the vitreous, a higher turn around in the anterior chamber, or differences in inflammatory cascades in both compartments.